2013
DOI: 10.1186/1757-7241-21-30
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation training in small-group setting – gender matters

Abstract: BackgroundWithin cardiopulmonary resuscitation external chest compressions (ECC) are of outstanding importance. Frequent training in Basic Life Support (BLS) may improve the performance, but the perfect method or environment is still a matter of research. The objective of this study was to evaluate whether practical performance and retention of skills in resuscitation training may be influenced by the gender composition in learning groups.MethodsParticipants were allocated to three groups for standardized BLS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Sopka et al demonstrated that the training environment interacts with learning of different genders. Female medical students improved CPR skills only in the female only group and not in mixed-gender groups [32].…”
Section: Discussionmentioning
confidence: 84%
“…Sopka et al demonstrated that the training environment interacts with learning of different genders. Female medical students improved CPR skills only in the female only group and not in mixed-gender groups [32].…”
Section: Discussionmentioning
confidence: 84%
“…Similar studies cited in the literature are carried out on practicing dentists or on dental graduates (Carvalho et al, 2008) (Laurent et al, 2009). The results of this study shows that one teaching session in basic life support skills is able to enhance dental students' awareness of importance of BLS skills and to increase their self-confidence in performing the procedure (Sopka et al, 2013). The results of the study will useful in developing countries where dental students either receive no teaching of emergency medical skills or where only lecture based teaching of emergency medical skills are done.…”
Section: Discussionmentioning
confidence: 84%
“…In a study conducted by Sopka et al (2015) in the first week, no significant difference was found in the level of knowledge of both sexes, but at the 8 th week, the female group looked superior to the group of male. 10 In the study of Adrian et al (2017) different results were obtained in the comparison to the value of BLS knowledge of women and men. Adrian et al's research state that women's group are only able to do BLS in less time than the men's group.…”
Section: Resultsmentioning
confidence: 99%